ANALYZING STUDENT'S DIFFICULTIES IN MASTERING VOCABULARY AT SMP PANGERAN ANTASARI - Laura Monica Lumbanraja (ELT (English Language Teaching Prima Journal), 2024)
The aim of this study is to ascertain the vocabulary comprehension challenges faced by students. Lack of vocabulary makes it difficult for students to communicate in a foreign language. Because of this, scholars are inspired to investigate the issues that students encounter and the methods they employ to resolve them. The descriptive qualitative research approach used in this study is centered on vocabulary challenges. Because the students' vocabulary knowledge was still lacking and the previous study results suggested that they had trouble understanding English classes, the researcher decided to use eighth grade students as research participants in this investigation. Researchers employed observation, document examination, and interviews to gather data. According to the study's findings, students encountered many. Difficulty learning vocabulary, such as having trouble recalling words in context. Out of all the students, only twelve were able to provide answers that were higher than the minimum. Aside from that, each student's average score is 57.5%, with a minimum of 40 and a maximum of 71. This demonstrates that pupils struggle with answering. Aside from that, they employ a variety of approaches to problem-solving, including teaching pupils new techniques, providing examples, and translating. determining the reasons behind the vocabulary learning challenges that kids face. The first language in which pupils struggle with word pronunciation is English. The second reason is grammatical form, since spoken and written English differ in this regard. Students do not pay attention to learning English further, know more words, and limit their time to sources of information about new vocabulary. Lastly, it's easy to forget the words.